PENERAPAN MODEL PEMBELAJARAN SHOW AND TELL PADA KETERAMPILAN BERBICARA MAHASISWA ASING DALAM PEMBELAJARAN BIPA 3 - Eldiana, Sheilla (Universitas Muhammadiyah Lampung, 2023)
ABSTRACTAt this time, Indonesian language learning continues to develop along with the progress of the times. One of the Indonesian language learning activities that are currently in great demand is learning BIPA or Indonesian for Foreign Speakers. The same applies to the process of learning Indonesian at school. In BIPA learning, foreign speakers are also taught 4 language skills. However, some foreign speakers often feel insecure to speak or tell stories in front of many people during BIPA learning. This is because foreign speakers are afraid of mispronouncing words, and embarrassed because they are not used to telling stories or speaking in front of new people. The purpose of this study was to determine the effect of the Show and Tell learning model on the speaking skills of foreign students in BIPA learning. This research uses descriptive qualitative method. Until the results found are the Show and Tell method is very influential in improving the speaking skills of foreign students in BIPA learning. Keywords: BIPA, Foreign Speaker, Speak